SWOT analysis of Hubei province outdoor sports clubs in the context of the leisure era - Jones, Harry; Wilson, Jennifer; Wang, Changxu (Cambridge Sport Science, 2025)
This study employs a questionnaire survey and utilizes the SWOT analysis method to evaluate outdoor sports clubs in Hubei Province against the backdrop of the emerging leisure era. The analysis reveals that these clubs possess significant locational advantages. However, they also face challenges such as the lack of scientific planning in the development of outdoor resources and insufficient management capabilities. Additionally, while the clubs are presented with development opportunities brought about by the rise of the central region strategy, they also confront risks due to inadequate risk prevention and emergency mechanisms. Establishing an industry development association, clarifying market positioning, and providing diversified and personalized services are identified as crucial strategies for club development. Relying on local characteristics and cultural landscapes, implementing regional cooperation and cross-industry linkages, and enriching the cultural connotations of outdoor sports are effective measures for the development of outdoor sports clubs in Hubei Province.